Epigenetic silencing of Kruppel like factor-3 increases expression of pro-metastatic miR-182. Issue 1 (1st December 2015) - Sachdeva, Mohit; Dodd, Rebecca D.; Huang, Zhiqing; Grenier, Carole; Ma, Yan; Lev, Dina C.; Cardona, Diana M.; Murphy, Susan K.; Kirsch, David G.
Highlights: Klf-3 is a novel transcriptional repressor of pro-metastatic miR-182 in sarcomas. Klf-3 suppresses a myogenic transcription factor MyoD1. Klf-3 is epigenetically silenced by DNA hypermethylation. Demethylating agents could potentially be used to modulate miR-182 levels as a therapeutic strategy. Abstract: Accumulating evidence indicates that microRNAs (miRs) regulate cancer metastasis. We have shown that miR-182 drives sarcoma metastasis in vivo by coordinated regulation of multiple genes. Recently, we also demonstrated that in a subset of primary sarcomas that metastasize to the lung, miR-182 expression is elevated through binding of MyoD1 to the miR-182 promoter. However, it is not known if there are also transcription factors that inhibit miR-182 expression. Defining negative regulators of miR-182 expression may help explain why some sarcomas do not metastasize and may also identify pathways that can modulate miR-182 for therapeutic benefit. Here, we use an in silico screen, chromatin-immunoprecipitation, and luciferase reporter assays to discover that Kruppel like factor-3 (Klf-3) is a novel transcriptional repressor of miR-182. Knockdown of Klf-3 increases miR-182 expression, and stable overexpression of Klf-3, but not a DNA-binding mutant Klf-3, decreases miR-182 levels. Klf-3 expression is downregulated in both primary mouse and human metastatic sarcomas, and Klf-3 levels negatively correlate with miR-182 expression. Interestingly, Klf-3 also negatively regulates MyoD1, suggesting an alternative mechanism for Klf-3 to repress miR-182 expression in addition to direct binding of the miR-182 promoter. Using Methylation Specific PCR (MSP) and pyrosequencing assays, we found that Klf-3 is epigenetically silenced by DNA hypermethylation both in mouse and human sarcoma cells. Finally, we show the DNA methylation inhibitor 5′Azacytidine (Aza) restores Klf-3 expression while reducing miR-182 levels. Thus, our findings suggest that demethylating agents could potentially be used to modulate miR-182 levels as a therapeutic strategy.